Perianal tuberculosis in an immunocompetent patient: A diagnostic enigma unraveled by caseating granulomas (Indian Journal of Case Reports, 2026)
Perianal tuberculosis (TB) is an exceptionally rare form of extrapulmonary TB (<1% of cases), often linked to immunocompromised states but increasingly reported in immunocompetent individuals in endemic areas. We describe the case of a 48-year-old immunocompetent male from a TB-endemic region presenting with a 4-year history of progressive left perianal nodular growths (initially solitary, evolving to multiple), associated with whitish seropurulent discharge for 1 year, perianal itching, and an unintentional 5 kg weight loss over 10 months. Examination showed multiple discharging sinuses at 1, 5, and 6 o’clock positions with a 3 × 2 cm irregular hyperpigmented nodular growth at 1 o’clock, 3 cm from the anal verge. Imaging revealed an 8 × 2 cm perianal abscess with sphincter involvement and fistulous tracts. Excisional biopsy demonstrated granulomatous inflammation with epithelioid histiocytes, Langhans giant cells, fibroblastic rimming, and central caseous necrosis, consistent with tuberculous etiology. Post-operative category I anti-tubercular therapy (2HRZE/4HR) led to complete resolution at 1-month follow-up. This case highlights perianal TB as a key differential in chronic perianal lesions in immunocompetent patients from endemic regions, stressing the role of early histopathological confirmation through caseating granulomas and combined surgical-medical management to prevent diagnostic delays and sphincter damage.